Проза 1912 - 1915 гг. - Кузмин М. А. (1999)
На тит. л. загл. не указано; Загл. указано на обороте тит. л. Экземпляры: аб. (2001) / Инвентарный номер: 43286 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 89 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6